Fabrication Of Porous Β_TCP Scaffold Via Freeze Drying Method - Ismail, Nurul Fatin Nabila
Beta-tricalcium phosphate (β-TCP) has been widely used for biomedical application. There are several methods to fabricate porous scaffolds including solvent casting, phase separation, rapid prototyping and electrospinning methods. In the present study, β-TCP scaffolds and alginate coated β-TCP scaffolds were fabricated using freeze drying method. β-TCP slurry was frozen and freeze dried for 24 hours followed by sintering process to form β-TCP scaffolds. The porous β-TCP scaffold were fabricated at different percentages of β-TCP powder used (10 wt%, 20 wt% and 30 wt%) and froze at different freezing temperature (-10°C, -20°C, -40°C and -80°C), in order to study the effect of these parameters on the pore formation of the scaffolds. Scanning electron microscopy (SEM) analysis for 30 wt% β-TCP scaffold frozen at -10°C revealed acceptable pore size distribution with majority pore size within the range of 102.65 μm to 372.90 μm. Furthermore, this scaffold also possessed highest compressive strength of 0.31 MPa. In order to investigate the effect of alginate coating on mechanical properties, 30 wt% β-TCP scaffold at freezing temperature of -10°C was selected to be impregnated with 5% of sodium alginate. After coating was completely done, Fourier transformed infrared spectroscopy (FTIR) analysis and SEM analysis were done. FTIR analysis identifies the existence of sodium alginate functional groups while SEM observation shows smoother surface. Compression test analysis shows that with the coating of sodium alginate on the -TCP scaffold increased in the compression strength value to 0.8 MPa from 0.31 MPa were obtained.